STRUKTUR DAN NILAI SOSIAL DALAM CERITA RAKYAT DI KABUPATEN MUARA ENIM - Tina Tina; Arif Ardiansyah (Universitas PGRI Palembang, 2017)
This study was aimed to describe structure and social values in of the Folktales. This study used descriptive qualitative method with objective approach. The data sources were based on the book entitled “Kumpulan Cerita Rakyat Kabupaten Muara Enim” published by Muara Enim Regency 2009. Based on findings and discussion, there were some characteristics which described the main character, such as, kind person, helpful, selfish, stubborn, arrogant, unfriendly, conceited, firm and calm. These characteristics were applied by the main character in that story. Furthermore, social values contained in that story were the relationship of human being in social life. People like a leader who had a kind and wise charachteristic. People have to appreciate each other to gain respect. There was no feeling to revenge though other people did a bad thing, especially in willing to sacrifice and devoted value to their parents. By this situation, we have to exploit district literature, especially folklore as “a bridge” to teach education values for our next generation to be better behaved, virtuous, and educated person. Keywords: analysis, structure, social value.